Hubungan Pengetahuan dengan Sikap Ibu Hamil Trimester III dalam Pemilihan Metode Kontrasepsi Jangka Panjang - I Gusti Ayu Widya Ananda Putri; Ni Made Dwi Mahayati; I Nyoman Wirata (Poltekkes Kemenkes Denpasar, 2022)
The use of MKJP in Bali in 2020 is 36.1% IUD, 0.6% MOP, 4.7% MOW, and 3.7% implant, from the MKJP achievement, which is 75%. Efforts made by the government with family planning programs. One of the factors for the lack of success of family planning programs is knowledge about the choice of contraceptive methods. The purpose of this study was to determine the relationship between knowledge and the attitude of pregnant women in the third trimester in choosing MKJP. This type of research is correlation analysis using a cross sectional approach. The study was conducted at UPTD Puskesmas I, East Denpasar District Health Office in April – May 2022. The study population was all third trimester pregnant women who did antenatal care. The sample size of 56 people with Spearman rank test obtained p value = 0.002. The value of r is 0.40, moderate correlation between knowledge and attitude variables. The conclusion in this study is that there is a relationship between knowledge and the attitude of pregnant women in the third trimester in choosing MKJP. The better the knowledge of third trimester pregnant women, the more positive the mother's attitude in choosing MKJP.